Impulsive Buying Behavior in Live-Streaming Shopping Mechanism: Do Fear of Missing Out Matter? - Adyantari, Api; Nugraha, Anastasius Yuan Cahya Didalunanda Eka; Dharomesz, Vonezyo Yupanzara (Review of Management and Entrepreneurship, 2025)
The aim of this study is to examine the factors influencing young consumers' impulsive buying behavior during TikTok Shop live-streaming flash sales, focusing on the effects of scarcity, discounts during live-streaming sales (DOLS), and fear of missing out (FoMO). The research targets Generation Y and Z, known for their high engagement with digital platforms. Using the Stimulus-Organism-Response (SOR) theory, the study explores how these factors interact to drive impulsive purchases. Data were collected from 295 respondents via an online survey and analyzed using SEM-PLS method to assess the relationships between the variables. The results indicate that both scarcity and DOLS significantly heighten FoMO, which acts as a psychological trigger for impulsive buying behavior. FoMO mediates the effect of scarcity and discounts on impulsive purchases, where scarcity creates urgency by limiting product availability, and DOLS entice consumers with time-sensitive deals. Additionally, the interactive nature of live-streaming enhances these effects by enabling real-time engagement with sellers. This study underscores the psychological impact of FoMO in live-stream shopping and provides valuable insights for marketers seeking to optimize social commerce strategies on platforms like TikTok.